Letter from James Curtis Booth to Campbell Morfit, July 26, 1880 - Booth, James Curtis (1880)
James Curtis Booth (1810-1888), writes to Campbell Morfit (1820-1897) lamenting his lack of leisure time and the passing of the years.
Keywords: Booth, James Curtis, 1810-1888; Morfit, Campbell, 1820-1897